Green synthesis of silver and zinc oxide nanoparticles with Thespesia populnea extract and investigation of their antioxidant potential against mouse mastitis model - Jayasri, A.; Eswara Prasad, P.; Kala Kumar, B. D. P.; Padmaja, K.; Shivakumar, P.; Anil Kumar, B.; Vidya, B. (Frontiers in Veterinary Science, 2025)
IntroductionBovine mastitis in dairy cattle is often complicated by antibiotic-resistant bacteria such as Staphylococcus aureus. Metal-based nanoparticles, especially plant-mediated nanoparticles have emerged as promising therapeutic tools for treating S. aureus-associated mastitis through the intramammary route. In this study, we synthesized, characterized, and assessed the antioxidant activity of Thespesia populnea nano silver particles (TPNS) and Thespesia populnea nano zinc oxide particles (TPNZ) derived from Thespesia populnea leaf extract (TPE). Silver nitrate and zinc acetate were reduced using TPE to synthesize TPNS and TPNZ, which were characterized by Scanning Electron Microscopy (SEM), UV–Visible Spectroscopy, Dynamic Light Scattering (DLS), and Zeta Potential analysis. The antioxidant activity of green-synthesized nanoparticles was evaluated in mastitis-induced mice.MethodsForty-eight female Swiss albino mice, 10–15 days of lactation, were divided into six groups (number of mice in each group-8). Group I served as the control, while mastitis was induced in groups II, III, IV, V and VI. Group III received T. populnea methanolic leaf extract (TPE); groups IV and V were treated with TPNS and TPNZ respectively; and group VI received Ceftriaxone.ResultsUV–Visible Spectroscopy confirmed the successful reduction of the metal ions to nanoparticles. SEM and DLS analysis revealed agglomerated morphologies with minimal variations in particle size. TPNS had a higher zeta potential than TPNZ, indicating a greater stability in the suspension. Mastitis-induced group showed significantly increased thiobarbituric acid reacting substances (TBARS) levels (p < 0.01) and significantly decreased Superoxide dismutase (SOD), Glutathione- S- transferase (GST), catalase (CAT), reduced glutathione (GSH), and glutathione peroxidase (GPx) activities (p < 0.01) compared to group I. Improvements were observed in groups IV, VI, V, and III.ConclusionThe TPNS-treated group (IV) showed the highest restoration of antioxidant activity, followed by the ceftriaxone (VI), TPNZ (V), and TPE-treated groups (III). These findings suggest that phytogenic nanoparticles exhibit higher antioxidant activity than TPE extract alone.